Advanced computational electromagnetic methods and applications - Yu, Wenhua 1960-; Li, Wenxing (Engineering professor); Elsherbeni, Atef Z.; Rahmat-Samii, Yahya (Artech House antennas and electromagnetics analysis library, 2015)
This new resource covers the latest developments in computational electromagnetic methods, with emphasis on cutting-edge applications